1987
DOI: 10.1159/000284514
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Year Follow-Up of Boys with Aggressive Conduct Disorder

Abstract: 53 boys with aggressive conduct disorder (ACD) and 36 with other psychiatric disorders were followed up after 2 years. Twenty-nine of the former (55%) still met the criteria for ACD; 24 did not. Persistence of the conduct disorder was predicted by the symptoms of hyperactivity and inattention. The data suggest that there are two types of ACD: one short-lived and quite benign, the other more likely to persist and more serious.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In the case of conduct disorder, there is some evidence for the existence of such subsamples. Stewart and Kelso (1987) stated that their "data suggest that there are 2 types of ACD [i.e., aggressive conduct disorder]; one short-lived and benign, the other more likely to persist and more serious" (p. 296). About 45% of the sample fell into the "benign" group (p. 296).…”
Section: Implications For Empirical Researchmentioning
confidence: 99%
“…In the case of conduct disorder, there is some evidence for the existence of such subsamples. Stewart and Kelso (1987) stated that their "data suggest that there are 2 types of ACD [i.e., aggressive conduct disorder]; one short-lived and benign, the other more likely to persist and more serious" (p. 296). About 45% of the sample fell into the "benign" group (p. 296).…”
Section: Implications For Empirical Researchmentioning
confidence: 99%
“…Gittelman et al, 1985). Taylor et al (in pwess) found that 81% of children presenting with mixed hyperactivity and conduct disturbance continued to have a disorder at follow-up, whereas only 28% of conduct disorders not associated with hyperactivity persisted over the same period (see also Stewart & Kelso, 1987;Magnusson, 1988;Taylor et al, in press;Gittelman et al, 1985;McGee et al, 1984a). Conversely, the prognosis of hyperactivity is worse when associated with conduct disturbance.…”
Section: Differences In Outcomementioning
confidence: 99%
“…Nearly 50% of PACD boys in our sample have associated ADHD. This is a common association (August et ai, 1983;Stewart & Kelso, 1987;McGee, Williams & Silva, 1984) and is unlikely to be coincidental. The fact that ADHD also distinguished our PACD from our SACD groups, however, is a confounding factor.…”
Section: Discussionmentioning
confidence: 91%
“…It is clear, however, that the genetic effect of having an antisocial parent is confounded with the influence on the child of the environment often created by such a parent. The children of an antisocial parent are at a higher risk to live in poverty, to come from a broken home, or to be placed out of the home (Behar & Stewart, 1982;Stewart & Kelso, 1987).…”
Section: Discussionmentioning
confidence: 99%